Surgical Treatment Of Peripheral Ossifying Fibroma: A Case Report - Kanehira, Beatriz Terumi Barreto; Pinheiro, Marina Rolo; Martins, Valber Barbosa; Motta Júnior, Joel; Albuquerque, Gustavo Cavalcanti de; Fayad, Flavio Tendolo; Oliveira, Marcelo Vinícius de (Journal of Oral Diagnosis, 2017)
The peripheral ossifying fibroma is a non-neoplastic gingival growth classified as a reactive hyperplastic inflammatory lesion. The pathogenesis is unknown. It is an injury that usually affects the anterior region of the maxilla and mandible and has a predilection for women that is most frequently found during the second decade of life. The purpose of this study is to report a case of peripheral ossifying fibroma in a 44-year-old patient with a history of increased volume in the anterior lingual region of the mandible with a 3-year history. Clinically it presented a well-delimited, pediculated lesion with firm and elastic consistency, with pale pink coloration and some erythematous patches. Computed tomography was requested, in which no image of cortical resorption or bone expansion was evidenced, however it was possible to visualize an image that suggested a small bone formation in the region of the lesion. Posteriorly, the patient underwent an excisional biopsy of the lesion. In the findings, the presence of oral mucosa with spindle cell proliferation was verified in the middle of a stromal with osteoid matrix and mature bone production. The treatment was the excision of the lesion with 1 year and 3 months follow-up without relapse.